1978
DOI: 10.1192/bjp.133.5.424
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Functions in Manic-Depressives: Effects of Lithium and Physostigmine

Abstract: Cognitive functions were investigated in seven manic depressive patients while on lithium, after two weeks off lithium, and after a subcutaneous injection of physostigmine while on lithium. Test performance was unaffected by lithium, but after physostigmine the I.Q. score of a shortened version of the WAIS was significantly increased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

1984
1984
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 11 publications
1
13
0
1
Order By: Relevance
“…In contrast to the delayed recall studies, studies examining long-term memory in bipolar patients on lithium compared to controls report either no deficit (Marusarz et al 1981) or even improved long-term memory in patients with depression (Kusumo and Vaughan 1977) Several lithium discontinuation studies investigating delayed verbal recall report deficits during their lithium administration periods (Christodoulou et al 1981;Shaw et al 1987;Kocsis et al 1993). However, an even greater number of studies fail to replicate this finding (Telford and Worrall 1978;Squire et al 1980;Smigan and Perris 1983;Sharma and Singh 1988). These studies also report intact long-term recall, being at odds with a single study reporting impaired long-term memory performance (Reus et al 1979).…”
Section: Lithium Immediate and Short-term Verbal Memorymentioning
confidence: 88%
See 1 more Smart Citation
“…In contrast to the delayed recall studies, studies examining long-term memory in bipolar patients on lithium compared to controls report either no deficit (Marusarz et al 1981) or even improved long-term memory in patients with depression (Kusumo and Vaughan 1977) Several lithium discontinuation studies investigating delayed verbal recall report deficits during their lithium administration periods (Christodoulou et al 1981;Shaw et al 1987;Kocsis et al 1993). However, an even greater number of studies fail to replicate this finding (Telford and Worrall 1978;Squire et al 1980;Smigan and Perris 1983;Sharma and Singh 1988). These studies also report intact long-term recall, being at odds with a single study reporting impaired long-term memory performance (Reus et al 1979).…”
Section: Lithium Immediate and Short-term Verbal Memorymentioning
confidence: 88%
“…Finally, discontinuation studies using double-blind crossover designs of lithium and placebo treatment found no difference in immediate memory and short-term memory (Squire et al 1980;Sharma and Singh 1988). Two more discontinuation studies testing short-term memory soon after discontinuation and as long as 12 months after lithium treatment also failed to note a lithium-induced deficit (Telford and Worrall 1978;Smigan and Perris 1983).…”
Section: Lithium Immediate and Short-term Verbal Memorymentioning
confidence: 92%
“…However, a 1-week period off lithium in prophylactically treated patients may fail to achieve a drug-free brain state. One study was not included in this section because the power analysis revealed an effect size below 0.20 (Smigan and Perris 1983) and two studies were not included because a power analysis could not be completed (Telford and Worrall 1978;Marusarz et al 1981).…”
Section: Psychiatric Patients On and Off Lithiummentioning
confidence: 98%
“…Chart reviews and patient surveys suggest that ap- Christodoulou et al (1981) No Demers and Heninger (1971) Engelsmann et al (1988) No Ghadirian et al (1983) No Kocsis et al (1987) Kocsis et al (1993) Reus et al (1979 Sharma and Singh (1988) Shaw et a1 (1987) Small et al (1972 No Squire et al (1980) Telford and Worrall (1978) No Glue et al (1987) Judd et al (1977b) Judd (1979) Karniol et al (1978 Kropf and Muller-Oerlinghausen (1979) Weingartner et al (1985) Patient vs. volunteer Joffe et al (1988b) Kusumo and Vaughan (1977) Volunteer samples Lund et al (1982) No "IPS = information processing speed, MS = motor speed, Cap = attentional capacig, Eg = vigilance, MC = mental control, RS = response set, SA = selective attention, Sim = simple condition, Com = complex condition, Imm = immediate recall, Int = msceptibility to interference, Ret = retention, Es = impaimnent found, No = no impairment found, Mix = equivocal results. proximately 42 to 52% of patients taking lithium complain of poor memory (Ghose, 1977;McCreadie and Morrison, 1985).…”
Section: Studies Of Patientsmentioning
confidence: 99%